Climate as a factor in the modern relief formation of the northeastern macroslope of Chornohora - Kostiv , L. Ya.; Shuber , P. M.; Burianyk, O. O.; Karabiniuk, M. M. (Man and Environment. Issues of Neoecology, 2023)
Purpose. To analyze climatic indicators that cause the formation and development of a wide range of geomorphological processes, including dangerous or catastrophic ones.Methods. Statistical, system analysis.Results. The research was based on the analysis of a number of climatic indicators (amount and intensity of precipitation, air and soil temperature, thickness of snow cover and water reserves in it) of the Pozhyzhevska snow avalanche station and the Laboratory of Landscape Monitoring of the Chornohora Geographical Station of the Ivan Franko National University of Lviv, which represent different oroclimatic zones.As a result of the study, the climatic indicators influencing the formation of modern relief processes of the northeastern slope of Chornohora were mainly established, and their heterogeneity in the different natural territorial complexes was characterized. Particular attention is paid to the processes of physical weathering, which are quite widespread and form the material for the further development of erosion and gravity processes. Their development is determined by significant temperature amplitudes and temperature transitions through 0°C. It has been established that an the Chornohora Geographical Station, daily air temperature amplitudes above 10°C are characteristic of 2/3 of the days of the warm period, above 15°C - on a third of the days, above 20°C in some cases, with a maximum value of 25.2°C. The daily amplitudes of temperature on the open soil surface above 20°C were recorded on half of the days of the warm period with repeated exceeding of 30°C. With depth, these indicators in the soil are smoothed out, but are still noticeable at a depth of 20 cm. The transition of the air temperature through 0°C (also one of the factors of defluxation) to the Chornohora Geographical Station was recorded on average on 98 days per year (including 38 in the snowless period). The amount and intensity of precipitation affecting the development of erosion processes, the formation of floods, mudflows, avalanches, and indirectly landslides and landslides.Conclusions. It has been found that the main climatic indicators that cause the formation and development of various geomorphological processes are precipitation, temperature, and snow cover thickness.